Sharing of IIUM Islamisation KRA projects - Md. Noon, Hazizan (2015)
The presentation was meant to brief the IIUM leaders of the Islamisation Key Result Area Projects for the year 2015 with special focus on IIUM Policies and Guidelines on Islamisation.